Analysis of IoT Enabled Architecture in Various Sectors and their Challenges - Kottursamy, Kottilingam (IRO Journal on Sustainable Wireless Systems, 2022)
Internet of Things (IoT) aims at being the quickest developing technology, with a huge effect on global life and manufacturing environment. The current mode of communication is either between humans or human and device; however, the concept IoT promises a bright future for the online platform where the mode of communication is machine-machine (M2M). Everything will be automated and smart, with a single tap. An effort has been made in this study to explore the key technologies, new innovative applications of IoT, as well as a comprehensive comparative literature survey. The survey helps in getting better knowledge on various real time applications and its impacts on the daily routine of human lives. The IoT tends to take numerous considerations from the commercial world and research community as a key advancement in the upcoming age of the Internet.
Keywords: Internet of Things; M2M; RFID; WSN; IoT applications